7,3′,4′-Trihydroxyisoflavone, a Metabolite of the Soy Isoflavone Daidzein, Suppresses α-Melanocyte-Stimulating Hormone-Induced Melanogenesis by Targeting Melanocortin 1 Receptor - Kim, Ji Hye; Lee, Jae-Eun; Kim, Taewon; Yeom, Myung Hun; Park, Jun Seong; di Luccio, Eric; Chen, Hanyong; Dong, Zigang; Lee, Ki Won; Kang, Nam Joo (Frontiers in Molecular Biosciences, 2020)
7,3’,4’-Trihydroxyisoflavone (7,3’,4’-THIF) is a metabolite of daidzein which is a representative isoflavone found in soybean. Recent studies suggested that 7,3’,4’-THIF exerts a hypopigmentary effect in B16F10 cells, however, its underlying molecular mechanisms and specific target protein remain unknown. Here, we found that 7,3’,4’-THIF, but not daidzein, inhibited α-melanocyte-stimulating hormone (MSH)-induced intracellular and extracellular melanin production in B16F10 cells by directly targeting melanocortin 1 receptor (MC1R). Western blot data showed that 7,3’,4’-THIF inhibited α-MSH-induced tyrosinase, tyrosinase-related protein-1 (TRP-1) and tyrosinase-related protein-2 (TRP-2) expressions through the inhibition of Microphthalmia-associated transcription factor (MITF) expression and cAMP response element-binding (CREB) phosphorylation. 7,3’,4’-THIF also inhibited α-MSH-induced dephosphorylation of AKT and phosphorylation of p38 and cAMP-dependent protein kinase (PKA). cAMP and Pull-down assays indicated that 7,3’,4’-THIF strongly inhibited forskolin-induced intracellular cAMP production and bound MC1R directly by competing with α-MSH. Moreover, 7,3’,4’-THIF inhibited α-MSH-induced intracellular melanin production in human epidermal melanocytes (HEMs). Collectively, these results demonstrate that 7,3’,4’-THIF targets MC1R, resulting in the suppression of melanin production, suggesting a protective role for 7,3’,4’-THIF against melanogenesis.